PENERAPAN LATIHAN KNEE TUCK JUMP TERHADAP HASIL LOMPAT TINGGI PESERTA EKSTRAKURIKULER MA MAZRO’ILLAH - Iqbal Andriansyah; Helvi Darsih; Ever Sovensi (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to determine the effect of Knee Tuck Jump training on the high jump results of extracurricular members at MA Mazro'illah. This research is an experimental study by providing a high jump test (pretest) before treatment and postest as the final high jump test. Samples were taken by saturated sampling technique, amounting to 11 people. The study used One Group Pretest-Postest Design which involved all high jump extracurricular participants at MA Mazro'illah. The results showed the effect of Knee Tuck Jump training on high jump results, the results obtained were tcount of 4.27> t table of 1.812 with dk = n-1 = 11-1 = 10, α = 0.05. By comparing the mean results obtained by the participants in taking the high jump test, the changes were better with an average difference of 7.27. Therefore it can be concluded that the Knee Tuck Jump exercise for high jump extracurricular participants at MA Mazro'illah has increased.